PENGARUH LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Damanik, Rizki Yulandari; Pasaribu, Dompak; Silitonga, Ivo Maelina (Jurnal Mahkota Bisnis (Makbis), 2024)
This study aims to examine the influence of liquidity, profitability, and leverage on the value of mining companies listed on the Indonesian Stock Exchange. Additionally, it seeks to investigate how dividend policy moderates this relationship. The original research sample comprised 62 organizations, however, after implementing the given criteria, only 16 companies met the requirements. The study employed secondary data and applied purposive sampling procedures for selecting the sample. The data analysis employed multiple linear regression models and moderation tests. The research findings suggest that liquidity has a somewhat detrimental and statistically insignificant effect on a company's worth. The profitability of a corporation has a somewhat positive and significant effect on its value, while leverage has a moderately negative and minor effect. The variables of liquidity, profitability, and leverage have a significant influence on the value of a company. The moderation study reveals that the dividend policy lacks the capacity to moderate the influence of liquidity on the firm's value. The dividend policy has the capacity to reduce the influence of profitability and leverage on the firm's value. The Adjusted R-Square value of 21.2% suggests that the company's value is influenced by the combined effects of liquidity, profitability, and leverage. Nevertheless, it is crucial to acknowledge that 79.8% of the company's worth is impacted by additional factors that were not taken into account in this study.